Effects of remnant preservation in anterior cruciate ligament reconstruction: A systematic review and meta-analysis - Xie, Huanyu; Fu, Zicai; Zhong, Mingjin; Deng, Zhenhan; Wang, Chen; Sun, Yijia; Zhu, Weimin (Frontiers in Surgery, 2022)
Background Compared with standard anterior cruciate ligament (ACL) reconstruction , it is controversial whether anterior cruciate ligament reconstruction (ACLR) with remnant preservation can lead to better clinical outcomes. We conducted a systematic study and meta-analysis to assess the differences in clinical efficacy between the two. Method We searched for clinical randomized controlled studies and cohort studies included in the Cochrane library, PubMed, and Embase from March 2012 to March 2022 in English. The included studies were ACLR with or without remant preservation, and the data were extracted and the quality of the included studies was assessed by two authors , respectively. Revman 5.4 was used for statistical analysis and conclusions were presented. Result Ten articles containing a total of 777 patients were finally included. There was no significant difference in postoperative Lachman test[OR=1.66, 95%CI(0.79, 3.49), P=0.18＞0.05], Tegner score[SMD=-0.13, 95%CI(-0.47, 0.22), P=0.46＞0.05], synovial coverage rate by second-look arthroscopy[OR=1.55, 95%CI(0.66, 3.56), P=0.32＞0.05], the rate of cyclops lesion[OR=3.92, 95%CI(0.53, 29.29), P=0.18＞0.05], joint range of motion[SMD=0.27, 95%CI(-0.13, 0.68), P=0.19＞0.05] and re-injury rate[OR=0.57, 95%CI(0.18, 1.74), P= 0.32＞0.05] between the two groups. There were statistically significant differences in postoperative Lysholm score[SMD = 0.98, 95% CI (0.32, 1.64), P = 0.004 < 0.05], International Knee Documantation Committee grade (IKDC grade)[OR=2.19, 95%CI(1.03, 4.65), P=0.04＜0.05], Pivot shift test[OR=1.71, 95%CI(1.06, 2.77), P=0.03＜0.05], KT1000/2000 arthrometer side-to-side difference[SMD=-0.22, 95%CI(-0.42, -0.03), P=0.02＜0.05], operation time[SMD=11.69, 95%CI(8.85, 14.54), P=0.00001＜0.05] and degree of tibial tunnel enlargement[SMD=-0.66, 95%CI(-1.08, -0.23), P=0.002＜0.05]. Conclusion This meta-analysis concluded that remnant preservation significantly had better results in terms of patient functional score (Lysholm, IKDC), knee stability(Pivot shift test, postoperative side-to-side anterior laxity) and tibial tunnel enlargement. In terms of complications(incidence of Cyclops lesions, range of motion, re-injury rate), no significant differences were seen between the two groups. Although many studies concluded that remnant preservation could bring better synovial coverage, this meta-analysis indicated that there is insufficient evidence to support it, possibly due to different remnant preservation procedures.The potential risks associated with longer operation times are also worth considering.